Characterization of the BnA10.tfl1 Gene Controls Determinate Inflorescence Trait in Brassica napus L. - Yongpeng Jia; Kaixiang Li; Haidong Liu; Lingxiong Zan; Dezhi Du (Agronomy, 2019)
Determinate inflorescences have a significant effect on the genetic improvement of rapeseed, so understanding the molecular function underlying the inflorescence trait may be beneficial to oilseed breeding. A previous study found candidate gene BnTFL1 (Terminal Flower 1) for control of the inflorescence trait on Brassica napus chromosome A10 (16,627−16,847 kb). However, little is known about the function of the BnTFL1 gene in B. napus. In this study, we firstly studied the formation of the shoot apical meristem and gene expression in indeterminate and determinate inflorescences; the results showed that the inflorescence architecture and BnA10.TFL1 expression showed significant differences in the shoot apex at the budding stage. Then, two alleles (named BnA10.TFL1 gene from indeterminate and BnA10.tfl1 gene from determinate) were cloned and sequence-analyzed; the results suggest that the open reading frame of the alleles comprises 537 bp, encodes 178 amino acids containing a conserved phosphatidylethanolamine-binding protein (PEBP) domain, and shares high similarity with Arabidopsis thaliana TFL1. To analyze the function of BnA10.TFL1, the BnA10.TFL1 gene was introduced into the determinate A. thaliana tfl1 mutant and B. napus 571 line by complementation experiment. The determinate traits were restored to indeterminate, and expression of BnA10.TFL1 was increased in the indeterminate shoot apex. These results reveal that BnA10.tfl1 is a gene controlling the determinate inflorescence trait. Moreover, the BnA10.TFL1 protein was localized to the nucleus, cytoplasm, and plasma membrane. Collectively, the results of this study help us to understand the molecular mechanism of determinate inflorescences and will provide a reliable research basis for the application of determinate inflorescences in B. napus.